Inducing adaptive emotion regulation by providing the students' perspective: An experimental video study with advanced preservice teachers. (February 2018) - Kumschick, Irina Rosa; Piwowar, Valentina; Thiel, Felicitas
Abstract: Is it possible to promote the use of reappraisal as an emotion regulation strategy during teachers' processing of classroom disruptions? We assume that teachers who are aware of the student perspective use reappraisal more often than teachers who are not aware of the student perspective. In order to test this hypothesis, we presented several video cases that illustrated a problematic classroom situation to preservice teachers in an experimental design. In addition, we presented supplementary information to the experimental group, in which the student who caused the disruption, reflected on his/her behavior by commenting on the teaching situation. In contrast, the video solely depicting the disruption was shown in the control group. Following a thorough stimulus evaluation check (both groups showed comparable emotional evaluation of the video cases), it could be demonstrated that the experimental group used significantly more reappraisal than the control group ( η 2  = 0.13), while suppression seemed not to be influenced by the student perspective—it was equally often used in both groups. Highlights: Within an experimental design, preservice teachers saw short videos of severely interrupted lessons. In this emotion-eliciting situation we sought to foster reappraisal of experienced emotions as an adaptive emotion regulation style. One way to do this is by taking the disruptive student's perspective into account. Perspective taking leads to a conceptual change in terms of cognitive reappraisal. The present study demonstrates that a cognitive reappraisal of experienced emotions could be induced by presenting the student's perspective.